Secondary cardiac lymphoma presenting with cardiac tamponade and cardiac mass: a case report - Wei Juan Lim; Neerusha Kaisbain; Rafidah Abu Bakar; Hafidz Abd Hadi; Ahmad Khairuddin Mohamed Yusof (Cardio-Oncology, 2024)
Abstract Background Cardiac tamponade as the presenting manifestation of systemic lymphoma is relatively uncommon. Pericardium is the commonest site of involvement in secondary malignancies with systemic lymphoma involving the heart in 20% of the cases. Case presentation We describe a case of a 78-year-old gentleman, who presented with symptoms of new onset cardiac failure, and hemodynamic compromise. An echocardiography revealed cardiac tamponade, necessitating an emergency pericardiocentesis. With the aid of multimodality imaging, he was found to have a right atrioventricular groove mass, widespread lymph node enlargement with bone and peritoneal involvement. Ultimately, a histopathological evaluation revealed a diagnosis of Diffuse Large B Cell Lymphoma (DLBCL). Conclusions Our case illustrates that a patient with DLBCL may present with cardiac tamponade as a result of metastasis. This diagnosis, although rare, is likely to be missed, which can cause fatal complications, such as cardiac tamponade, fatal arrhythmias or sudden cardiac death.